Impact and Potential Risk of Acute Myocardial Infarction on Consultation Type During the COVID-19 Pandemic: A Single-Center Experience - Furui, Masato; Kawajiri, Kenji; Yoshida, Takeshi; Kakii, Bunpachi; Oshiro, Norikazu; Asanuma, Mai; Nishioka, Hiroaki; Wada, Hideichi (Cardiology and Cardiovascular Medicine, 2023)
Backgraound: Studies considering consultation types, such as walk-in, direct arrival by emergency medical service, or referral are rare in the coronavirus disease 2019 (COVID-19) era. The aim of this study was to compare the time course and outcome of acute myocardial infarction (AMI) and to examine the relation of the consultation types (walk-in and referral) with the time course during COVID-19 era. Methods: In total, 503 patients who underwent emergency percutaneous coronary intervention between January 2011 and December 2021 at our institution were reviewed retrospectively. The AMI time course, mechanical complications, and mortality before and after the COVID-19 emergency declaration were compared. Results: Overall, 426 patients with ST-segment elevation myocardial infarction (STEMI) and 77 patients with non-STEMI were identified. In STEMI patients, the onset-to-door time was prolonged (181 vs. 156 min, P=0.001) and mechanical complications worsened (7.8% vs. 2.6%, P=0.025) after the emergency declaration, compared with the findings before the pandemic. Multivariable analysis revealed that post-declaration, age, walk-ins, and referrals became independent risk factors for mechanical complications in STEMI patients. Conclusions: Arrival by referral or walk-in which can cause treatment delay was identified as an independent risk factor of mechanical complications in addition to age and the time period post-declaration. Longitudinal research is needed to corroborate these potential risks during COVID-19 era.